PENGARUH STORE ATMOSPHERE, SERVICE QUALITY DAN SOCIAL MEDIA MARKETING TERHADAP CUSTOMER SATISFACTION DI SPREAD CAFE BY TOOTOOMOO SURABAYA - Theodora Kezia Sudibyo; Callista Fortune; Irra Chrisyanti Dewi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to analyze the impact of store atmosphere, service quality, and social media marketing on customer satisfaction at Spread Cafe by Tootoomoo Surabaya. In this competitive digital era, understanding the factors that influence customer satisfaction is crucial for the sustainability of businesses, especially in the F&B industry. This study uses a quantitative method with data collection through questionnaires distributed to Spread Cafe customers. A total of 124 respondents were selected as the sample, using purposive sampling technique. The data collected were then analyzed using PLS-SEM with the aid of SmartPLS 4.0 software. The analysis results show that store atmosphere, service quality, and social media marketing each have a positive and significant effect on customer satisfaction. These findings indicate that a comfortable cafe atmosphere, excellent service quality, and effective social media marketing strategies can enhance overall customer satisfaction. This research contributes to cafe managers in formulating marketing and operational strategies focused on customer experience. Furthermore, the results also strengthen the literature regarding the factors that influence customer satisfaction in the context of the local F&B industry.